MANAGEMENT OF THE POTENTIAL OIL AND GAS ENTERPRISE UNDER THE OPERATIONAL MODEL TRANSFORMATION CIRCUMSTANCES (ON THE EXAMPLE OF THE KHRESTYSHCHE DDW) - Овецька, Ольга; Ткачук, Руслана (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The purpose of this article is to analyze the strategic prerequisites for the development of the potential of the oil and gas company and to develop practical recommendations for managing the production potential of the drilling company (on the example of Khrestishche DDW) in the transformation processes of the Naftogaz Group. The urgency of studying the problems of managing the potential of oil and gas companies in accordance with the strategic guidelines for the development of Ukraine's oil and gas sector defined by the Energy Strategy of Ukraine until 2035 "Safety, Energy Efficiency, Competitiveness" and the new corporate strategy of Naftogaz of Ukraine. The main results of activity and strategic tasks of the division "Technical support" development according to the new operational model are considered. Due to the analysis of the Khrestyshche DDW map the directions of development of production potential of the researched enterprise with orientation of operational activity on intensification of technological processes, replacement of critically worn out equipment, energy and resource saving, increase of labor safety and environmental protection are formed. Based on the analysis of the definition of capacity and generalization of conceptual approaches to enterprise capacity management, the following conclusions are made: the importance of adequate assessment, formation and management of oil and gas enterprise capacity due to the fact that the potential demonstrates the essence of operational processes and also extrapolates trends in the development of the transformation model in the future; the formation of the potential of the drilling company should be considered in the context of purposeful transformation activities and the introduction of a new operational model, which is based on intensive development and increase of the total potential of the enterprise to achieve its strategic goals.